2020
DOI: 10.1186/s12884-020-03271-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of preterm birth in Ethiopia: systematic review and meta-analysis

Abstract: Background Globally, complications of preterm birth are among the most common cause of neonatal mortality. In Ethiopia, the neonatal mortality reduction is not worthy of attention. Hence, this study reviewed the prevalence of preterm birth and factors associated with preterm birth in Ethiopia. Methods The review protocol of this study has been registered in PROSPERO (CRD42017077356). The PRISMA guideline was followed for this review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 68 publications
4
29
2
1
Order By: Relevance
“…Currently, there is growing national attention focused on reducing neonatal mortality in Ethiopia; however, information regarding the relative importance of preventative strategies and predictors for newborn morbidity and mortality remains limited in Ethiopia. A meta-analysis reported on preterm birth and the effect of hypertension, multiple pregnancies, antepartum hemorrhage, and chronic illness on preterm birth [ 32 ], yet the pooled prevalence was limited to only four of the nine regions in the country and did not address modifiable risk factors for preterm birth such as intimate partner violence (IPV) and maternal malnutrition. Hence, there was inconclusive and inconsistent findings across the country [ 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is growing national attention focused on reducing neonatal mortality in Ethiopia; however, information regarding the relative importance of preventative strategies and predictors for newborn morbidity and mortality remains limited in Ethiopia. A meta-analysis reported on preterm birth and the effect of hypertension, multiple pregnancies, antepartum hemorrhage, and chronic illness on preterm birth [ 32 ], yet the pooled prevalence was limited to only four of the nine regions in the country and did not address modifiable risk factors for preterm birth such as intimate partner violence (IPV) and maternal malnutrition. Hence, there was inconclusive and inconsistent findings across the country [ 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, all MNH trainings should cover the management of the HIV exposed infant [ 38 ]. As the prevalence of preterm births in Ethiopia (10.5%) and Nepal (9.3%) is high, this finding is particularly relevant and trainings should include special care for preterm births [ 39 , 40 ]. Newborn interventions in CEmONC were found to be generally weak in both countries and need additional strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…The national-level prevalence of preterm birth in Ethiopia was high. A systematic review and meta-analysis showed that the overall pooled prevalence of preterm birth in Ethiopia was 10.48% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%